BASMALAH DALAM SURAH AL-FATIHAH VERSI QIRAAT SAB’AH DAN IMPLIKASINYA TERHADAP HUKUM 4 MAZHAB - Maskanah Maskanah (JOURNAL OF LAW AND NATION, 2022)
All the companions of the Prophet agreed to write Basmalah at the beginning of the holy verses of the Qur'an. They agreed that the sentence Basmalah contained in the letter An-Naml is one of the verses of the letter. However, they have different opinions about the basmalah written at the beginning of the sura, including at the beginning of sura al fatihah. This research aims to find out the basmalah in the qiraat sab'ah version of surah al-Fatihah and its implications for the laws of the 4 schools of thought. The focus of this research is what is qiraat sab'ah? how about the basmalah in the qiraat sab'ah version of surah al-Fatihah? What are the implications of Basmalah in the qiraat sab'ah version of surah al fatihah on the laws of the 4 mazhab of thought? This research is a qualitative research using a library research approach. In exploring legal istimbath related to this research using content analysis techniques. The results of this study are that Imam Malik believes that Basmalah is not part of surah Al-Fatihah, and therefore it is not read when reading Al-Fatihah in prayer. The Hanafi school of thought and the Hanbali school of thought are of the opinion that Basmalah is recited in prayer when reading surah Al- Fatihah but not aloud. This means that those who follow the readings of Ahlu Medina, Basra and Syam, namely Imam Nafi', Ibn Amir and Abu 'Amr, reading Basmalah are not included in the Fatihah surah. Imam Syafi'i believes that Basmalah is the first verse of surah Al-Fatihah, so basmalah must be read when reading sura Al-Fatihah. This means who follows the readings of the Meccan and Kufah qiraat experts, namely Imam Ibn Katsir, Imam 'Ahim, Imam Kisa'i and Imam Hamza Basmalah included in surah Al-Fatihah.